2020
DOI: 10.1002/gps.5369
|View full text |Cite
|
Sign up to set email alerts
|

Development of a short‐form version of the Reading the Mind in the Eyes Test for assessing theory of mind in older adults

Abstract: Background: The Reading the Mind in the Eyes test (RMET) is a 36-item assessment for theory of mind (ToM) performance. While this measure has been shown to be sensitive to age-related ToM difficulties, there are no established cutoffs or guidelines currently available that are specific to older adults. This article seeks to validate a short-form version of the RMET appropriate for use in such populations. Methods: Cross-sectional data from 295 participants (mean age 86 years) from the Sydney Memory and Ageing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
1
7
2
Order By: Relevance
“…Thus, the aim of the present study was to present further validity evidence on the RMET-10 in three large, independent datasets. Across three samples (total N = 3,121), we found that the RMET-10's hypothesized unidimensional model provided an excellent fit to the data (see Table 2), corroborating the favorable conclusions reached by Olderbak et al (2015) and Chander et al (2020) regarding the RMET-10's factorial validity. Despite observing strong factorial validity evidence, however, the reliability estimates obtained in the present study fell somewhat short of conventionally cited guidelines (e.g., .70 or .80).…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Thus, the aim of the present study was to present further validity evidence on the RMET-10 in three large, independent datasets. Across three samples (total N = 3,121), we found that the RMET-10's hypothesized unidimensional model provided an excellent fit to the data (see Table 2), corroborating the favorable conclusions reached by Olderbak et al (2015) and Chander et al (2020) regarding the RMET-10's factorial validity. Despite observing strong factorial validity evidence, however, the reliability estimates obtained in the present study fell somewhat short of conventionally cited guidelines (e.g., .70 or .80).…”
Section: Discussionsupporting
confidence: 72%
“…Like the original validation studies of the RMET-10 (Olderbak et al, 2015), all data were solely collected from convenience samples of United States residents. As such, between our own results and those of Olderbak et al (2015) and Chander et al's (2020) study of Australian adults, we are limited in what can be concluded regarding the RMET-10's validity in other cultural contexts (e.g., non-Western contexts where emotion categories, vocabulary or display norms may differ, among many other factors). A clear priority for future research is thus to test the RMET-10 in other contexts.…”
Section: Limitations Future Directions and Constraints On Generalitycontrasting
confidence: 69%
See 3 more Smart Citations